2014
DOI: 10.1051/0004-6361/201423517
|View full text |Cite
|
Sign up to set email alerts
|

MAGIC reveals a complex morphology within the unidentified gamma-ray source HESS J1857+026

Abstract: Aims. HESS J1857+026 is an extended TeV gamma-ray source that was discovered by H.E.S.S. as part of its Galactic plane survey. Given its broadband spectral energy distribution and its spatial coincidence with the young energetic pulsar PSR J1856+0245, the source has been put forward as a pulsar wind nebula (PWN) candidate. MAGIC has performed follow-up observations aimed at mapping the source down to energies approaching 100 GeV in order to better understand its complex morphology. Methods. HESS J1857+026 was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…(Deil et al 2015;Donath et al 2017), and in ongoing surveys by the recently completed HAWC array (Abeysekara et al 2017). Similar sources have also been reported by MILAGRO (Abdo et al 2007), ARGO (Bartoli et al 2013), VERITAS (Weinstein et al 2009) and MAGIC (Aleksić et al 2014). As of August 2017, TeVCat (Wakely & Horan 2008) lists ∼55 sources located within ∼ 10 • of the Galactic Plane with type "unidentified".…”
Section: Hvc Accretion Origin Of High-energymentioning
confidence: 55%
“…(Deil et al 2015;Donath et al 2017), and in ongoing surveys by the recently completed HAWC array (Abeysekara et al 2017). Similar sources have also been reported by MILAGRO (Abdo et al 2007), ARGO (Bartoli et al 2013), VERITAS (Weinstein et al 2009) and MAGIC (Aleksić et al 2014). As of August 2017, TeVCat (Wakely & Horan 2008) lists ∼55 sources located within ∼ 10 • of the Galactic Plane with type "unidentified".…”
Section: Hvc Accretion Origin Of High-energymentioning
confidence: 55%
“…Over 15 sources within this region were discovered by H.E.S.S. Similar surveys within this region have been performed by Milagro (Abdo et al 2007) and ARGO (Bartoli et al 2013b), along with targeted observations by the IACTs VERITAS and MAGIC (for example, Albert et al 2006;Acciari et al 2009;Aleksić et al 2012Aleksić et al , 2014Aliu et al 2014a). At lower energies, the Fermi Large Area Telescope (Fermi-LAT) has published its third source catalog in the 100 MeV-300 GeV energy range (3FGL), based on the first four years of science operation (Acero et al 2015).…”
Section: Introductionmentioning
confidence: 60%
“…Both of the HESS sources were detected as extended, with HESS J1857+026 as the larger of the two. Aleksić et al (2014) reported energy-dependent morphology for HESS J1857+026 with two distinct components, MAGIC J1857.2+0263 and MAGIC J1857.6+0297. These sources cannot be resolved with these data from the partial HAWC array.…”
Section: Source Detectionsmentioning
confidence: 99%